Analisis Value Chain Guna Mencapai Strategi Cost Leadership Dalam Meningkatkan Efisiensi Biaya (Studi pada Perusahaan "X" di Sidoarjo) - Heri Widodo, (Bisnis dan Manajemen, 2008)
This research aim for knowing, how   value chain analysis was do in company value chain for achieve cost leadership strategy in increasing cost efficiency.According to value chain analysis explained what  activities made company value chain , therefore will be know value added activity  and non value added activity.In the same way, research in value chain analysis can showing company activity . This activity can devided into primary activity and supporting activity, value added activity and non value added activity and cost trigger, therefore cost efficiency can be achieve which reducing and eliminate  waste activity.In conclusion, this research can be a input  for company, while taking corpaorate strategy to increase profit and give value added for customer. Value chain analysis will achieve cost leadership can increase company competitive advantage becase it can increase cost efficiency.